Estonian and Finnish teachers’ experiences of textile craft purposes in basic education - Veeber, Eva; Syrjäläinen, Erja; Kokko, Sirpa (FormAkademisk, 2023)
This study investigates the purpose of craft education and how this purpose manifests according to Estonian and Finnish textile craft teachers. Semi-structured interviews were conducted with eight teachers. The interview transcriptions were analysed using a qualitative content analysis method, resulting in seven main categories that revealed how the purpose of learning crafts manifests in compulsory basic education. According to the teachers, besides enhancing learning practical skills and how to use hands more skilfully, consistent craft making also enhances students’ versatile thinking; generates holistic practices; nurtures confidence, perseverance and sense of responsibility; shapes mature ways of expressing feelings; develops personal authenticity; and promotes social connectedness.